Comparison of three drought indices and their evolutionary characteristics in the arid region of northwestern China. (6th February 2017) - Wang, Huaijun; Pan, Yingping; Chen, Yaning
Abstract: Drought evolutions in the arid region of northwestern China from 1960 to 2010 were analyzed based on the standardized precipitation index (SPI), the standardized precipitation‐evapotranspiration index (SPEI), and the self‐calibrated Palmer drought severity index (SC‐PDSI). All three forms of drought indices were significantly correlated with each other. No statistically significant differences were found for the severity of drought, as assessed by both the SPI and SPEI. The SC‐PDSI was generally an index representing water deficits at a medium period. For the entire geographical area of study, wet conditions dominated during 1987–2010, whereas persistent drought conditions occurred from 1960 to 1986.